A relação entre orçamento e resiliência de empresas em cenários de flutuação econômica - Lopes, Sócrates Dantas (Universidade do Vale do Rio dos Sinos, 2023)
This research aims to analyze the correlation between budget utilization and the resilience of companies during periods of economic fluctuations, taking into account performance and the budget structure model used in a sample of 95 listed B3 companies.The study period spans from the 1st quarter of 2017 to the 3rd quarter of 2022, during which five budget structure models and ten budget functions were considered for design and application. To achieve the objectives, the research employed Wilcoxon statistical tests, Principal Components Analysis, Clustering Analysis using Ward's method, and Fisher's Exact test. Hypotheses were tested through the application of the Wilcoxon test, considering the relationship between budget functions and performance within each group. The study concluded that it has statistically significant differences among various budget structures models concerning organizational resilience. It was found that in the Standard budget structure the number of companies affected by the crisis was statistically greater than those not affected and the number of companies with resilient performance is statistically greater than non-resilient companies, that is, in the Standard budget structure the proportion between resilient and non-resilient companies is statistically significant, a result not achieved in the other budget structures studied.
Keywords: Estruturas orçamentárias; Resiliência organizacional; Abordagem configuracional; Budget structures; Organizational resilience; Configurational approach; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis